1991
DOI: 10.2307/1941556
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and Phosphorus Effects on Secondary Succession Dynamics on a Semi‐Arid Sagebrush Site

Abstract: A sagebrush steppe community in northwestern Colorado was disturbed in 1984 and subjected to annual applications of nitrogen and phosphorus, and successional responses were studied over a 5—yr period. Phosphorus was not found to be significant but nitrogen did significantly affect succession for all years except the first. Three seral groups developed on the non—fertilized plots, the first two dominated by annuals and lasting 3 yr, the third transitional and dominated by perennials. The addition of N altered t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
98
2
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(110 citation statements)
references
References 45 publications
7
98
2
3
Order By: Relevance
“…The nutrient supply is one of the major sources for promoting plant productivity and diversity in grasslands (Reynolds and Haubensak 2008). Limiting resources are the key factors that determine plant diversity, vegetation community composition, and successional dynamics (Mclendon and Teclente 1991;Hooper et al 2005). The plants with higher competitive abilities have access to a greater proportion of available resources.…”
Section: Discussionmentioning
confidence: 99%
“…The nutrient supply is one of the major sources for promoting plant productivity and diversity in grasslands (Reynolds and Haubensak 2008). Limiting resources are the key factors that determine plant diversity, vegetation community composition, and successional dynamics (Mclendon and Teclente 1991;Hooper et al 2005). The plants with higher competitive abilities have access to a greater proportion of available resources.…”
Section: Discussionmentioning
confidence: 99%
“…Cheatgrass responds dramatically to the availability of nitrogen, to the detriment of perennial plants, since it directly depletes nitrogen from the soil and interferes with N 2 -fixation by the biological soil crust (Kay and Evans 1965, Wilson et al 1966, McLendon and Redente 1991, Evans et al 2001. Although germination and root growth characteristics make cheatgrass a very aggressive plant, it tends to be most competitive with native vegetation after disturbance .…”
Section: Modeling Risk Of Cheatgrass Displacement Of Sagebrush and Otmentioning
confidence: 99%
“…Increased nitrogen availability due to disturbance in semiarid climates has been shown to delay succession by allowing annuals to establish and maintain dominance of the recovering plant community. McClendon and Redente (1991) conducted an experiment in the Piceance Basin in western Colorado where they disturbed the soil by scraping off the top 2 inches and mixing the next 14 inches by cultivating, which decreased the soil seed reserve by an estimated 90%. They provided annual additions of nitrogen and phosphorous for a period of 5 years and compared the resulting plant communities to similarly disturbed plots where no amendments were made.…”
Section: Downy Brome and Natural Plant Communitiesmentioning
confidence: 99%
“…This favors its germination, establishment, and dominance on sites. Research has shown that decreasing the amount of available nitrogen (by increasing soil carbon) disfavors downy brome (McClendon and Redente 1991;Paschke et al 2000). There currently are no practical methods commercially available to increase soil carbon thus, decrease available nitrogen.…”
Section: Other Cultural Considerationsmentioning
confidence: 99%